A retrospective study of multiple sclerosis in Siriraj Hospital, Bankok, Thailand - Sasitorn Siritho (2018)
Objective: To determine the demographic and clinical data of Thai multiple sclerosis (MS) patients. Methods: A retrospective study of 72 patients attending the MS clinic at Siriraj Hospital, Mahidol University, Thailand between January 1997 and June 2004. Results: Fifty-eight patients (81%) were classified as clinically definite MS, 5 (7%) as Devic's syndrome, and 9 (13%) as possible MS. There were 62 females (86%) and 10 males (14%). Age at onset was 33 ± 12 years with a mean relapse rate of 1.2 ± 1.0 attacks per annum. None had a family history of MS. Visual impairment (53%) was the most common manifestation. Only 16% had classic (western) form of MS. Positive oligoclonal bands were found in 21%, visual evoked potentials with a typical delayed latency in 28%. MRI brain lesions compatible with McDonald's criteria were seen in only 24%, and spinal MRI brain longer than 2 vertebral bodies in 62%. The mean Kurtzke's Expanded Disability Status Scale (EDSS) was 3.0. Conclusions: Thai MS patients had much more female occurrence, no family history, common optico-spinal form, long spinal MRI lesions and low positive CSF oligoclonal bands.